2013
DOI: 10.1158/1055-9965.epi-12-1422
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nicotine and Carcinogen Exposure with Water Pipe and Cigarette Smoking

Abstract: Background Smoking tobacco preparations in a water pipe (hookah) is widespread in many places of the world and is perceived by many as relatively safe. We investigated biomarkers of toxicant exposure with water pipe compared to cigarette smoking. Methods We conducted a cross-over study to assess daily nicotine and carcinogen exposure with water pipe and cigarette smoking in 13 people who were experienced in using both products. Results While smoking an average of 3 water pipe sessions compared to smoking 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 27 publications
6
99
1
7
Order By: Relevance
“…28 Urine concentrations of total NNAL were measured by LC-MS/ MS. 30 The following metabolites of volatile toxicants (derivates of mercapturic acid, MA) were determined using an LC-MS/MS method: 2-hydroxyethylmercapturic acid (HEMA), 2-hydroxy-3-buten-1-ylmercapturic acid and isomers (MHBMA), 3-hydroxy-1-methyl propylmercapturic acid (HPMMA), 3-hydroxypropylmercapturic acid (3HPMA), S-phenylmercapturic acid (SPMA), 2-carbamoylethylmercapturic acid (acrylamide mercapturic acid (AAMA), 2-cyanoethylmercapturic acid (CNEMA), and 2-hydroxypropylmercapturic acid (2HPMA). 31 The following metabolites of polycyclic aromatic hydrocarbons (PAHs) (free plus conjugated) were determined using LC-MS/MS: 2-naphthol, 1-hydroxyfluorene, 2-hydroxyfluorene, 3-hydroxyfluorene, 1-hydroxyphenanthrene, 2-hydroxyphenanthrene, 3+4-hydroxyphenanthrene (sum); and 1-hydroxypyrene. 32 Methods and analytical runs were validated using established procedures.…”
Section: Biomarkers Of Exposure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…28 Urine concentrations of total NNAL were measured by LC-MS/ MS. 30 The following metabolites of volatile toxicants (derivates of mercapturic acid, MA) were determined using an LC-MS/MS method: 2-hydroxyethylmercapturic acid (HEMA), 2-hydroxy-3-buten-1-ylmercapturic acid and isomers (MHBMA), 3-hydroxy-1-methyl propylmercapturic acid (HPMMA), 3-hydroxypropylmercapturic acid (3HPMA), S-phenylmercapturic acid (SPMA), 2-carbamoylethylmercapturic acid (acrylamide mercapturic acid (AAMA), 2-cyanoethylmercapturic acid (CNEMA), and 2-hydroxypropylmercapturic acid (2HPMA). 31 The following metabolites of polycyclic aromatic hydrocarbons (PAHs) (free plus conjugated) were determined using LC-MS/MS: 2-naphthol, 1-hydroxyfluorene, 2-hydroxyfluorene, 3-hydroxyfluorene, 1-hydroxyphenanthrene, 2-hydroxyphenanthrene, 3+4-hydroxyphenanthrene (sum); and 1-hydroxypyrene. 32 Methods and analytical runs were validated using established procedures.…”
Section: Biomarkers Of Exposure Analysismentioning
confidence: 99%
“…33,34 Lower limits of quantitation are provided in Supplementary Table 2, and the details on quality control measures for the various assays are listed elsewhere. [30][31][32]35 Urine creatinine was measured in the San Francisco General Hospital clinical laboratory using a standard colorimetric assay.…”
Section: Biomarkers Of Exposure Analysismentioning
confidence: 99%
“…Studies have identified carcinogens and toxicants such as polyaromatic hydrocarbons and volatile aldehydes in hookah tobacco smoke and biomarkers of these toxicants in the urine of hookah smokers (Al Rashidi, Shihadeh, & Saliba, 2008;Daher et al, 2010;Jacob et al, 2011Jacob et al, , 2013.…”
mentioning
confidence: 99%
“…Smoking cessation programs and anti-smoking campaigns should emphasize that recent evidence on the health hazards of first-, second-and third-hand tobacco smoking. [36][37][38][39][40][41] The findings showed that former smokers less agreed than never smokers to ban smoking in restaurants. The dependency on nicotine that was experienced by former smokers may have contributed to that lenient attitude toward enforcing smoking banning.…”
Section: Discussionmentioning
confidence: 97%